Media Pembelajaran Pengenalan Fauna Berbasis Virtual Reality - Zaini, TM; Wulandari, Ayu (Politeknik Negeri Sriwijaya, 2020)
The use of computers or smartphones has penetrated in various fields of life, including education. Learning the introduction of fauna to kindergarten students is generally conveyed using learning media, namely in the form of books, electronic media or visit to the zoo where the use of conventional learning media is currently less attractive and not interactive and requires special time to visit the zoo. The development of virtual reality technology enables the application of learning media applications that present virtual objects in the form of multimedia content such as sound, images, text, video and animation. The method used for the development of virtual reality applications is by using multimedia development stages, namely concept, design, material collecting, assembly, testing, and distribution. The test results show that the application gets a positive response which can be seen from the enthusiasm of using virtual reality applications and the high score quiz obtained.Â Thus it can be concluded that this application is able to improve Kindergarten students' understanding of the fauna that is used both mobile and offline.